## General Composition Shown above is a general formulation of composition of operations in dependent type theory, as derived below.

## Tuple Functors

If $n$ is a natural number, we write $n \colon \mathbb N$ and say "$n$ has type $\mathbb N$." (For the reader unfamiliar with type theory, it's safe in the beginning to think of this as meaning $n\in \mathbb N$.)

For $n \colon \mathbb N$, we denote and define $\underline{n} = \{0, 1, \dots, n-1\}$.

For $m \colon \mathbb N$, denote and define the $\mathrm{mtuple}$ functor on Set as follows:

• on objects: if $A$ is a Set, then $\mathrm{mtuple} A = \{(a_{0}, \dots, a_{m-1}) \mid a_{i} \colon A\}$

• on arrows: if $f \colon A \to B$ is a function from the set $A$ to the set $B$, then $\mathrm{mtuple} f \colon \mathrm{mtuple}A \to \mathrm{mtuple}B$ is defined for each $(a_{0}, \dots, a_{m-1})$ of type $\mathrm{mtuple}A$ as follows: $$\mathrm{mtuple}f (a_0, \dots, a_{m-1}) = (f a_0, \dots, f a_{m-1}),$$ which inhabits the type $\mathrm{mtuple} A$.

Notice that $\mathbf a$ has type $\mathrm{mtuple} A$ iff we can represent $\mathbf a$ as a function of type $\underline{m} \to A$; that is, iff we can represent the mtuple $(a_0, \dots, a_{m-1})$ as a function, $\mathbf a$, where $\mathbf a(i) = a_i$ for each $0\leq i < n$. Thus, we have the following equivalence of types: $\mathrm{mtuple} A \cong \underline{m} \to A$.

Let $\mathbf m = (m_0, \dots, m_{n-1}) \colon \mathrm{ntuple} \mathbb N$. Define the $\mathbf{mtuple}$ functor as follows:

• on objects: if $A$ is a Set, then $$\mathbf{mtuple} A = \{((a_{00}, \dots, a_{0(m_1-1)}), \dots, (a_{(n-1)0}, \dots, a_{(n-1)(m_n-1)})) \mid a_{ij} \colon A\}$$ (We may write $\mathbf a_i$ in place of $(a_{i0}, \dots, a_{i(k-1)})$, if $k$ is clear from context.)

• on arrows: if $f$ is a function from the set $A$ to the set $B$, then $\mathbf{mtuple} f \colon \mathbf{mtuple}A \to \mathbf{mtuple}B$ is defined for each $(\mathbf a_1, \dots, \mathbf a_n)$ in $\mathbf{mtuple}A$ as follows: \begin{align*}\mathbf{mtuple} f (\mathbf a_1, \dots, \mathbf a_n) &= (\mathrm{m_1tuple}f \mathbf a_1, \dots, \mathrm{m_ntuple}f \mathbf a_n)\ &= ((f a_{11}, \dots, f a_{1m_1}), \dots, (f a_{n1}, \dots, f a_{nm_n})).\end{align*}

Notice that $\mathbf a_i$ has type $\mathrm{m_ituple} A$ iff it can be represented as a function of type $\underline{m_i} \to A$; that is, iff the tuple $(a_{i0}, \dots, a_{i(m_i-1)})$ is (the graph of) the function defined by $\mathbf a_i(j) = a_{ij}$ for each $0\leq j < m_i$. Thus, if $\mathbf m = (m_0, \dots, m_{n-1}) \colon \mathrm{ntuple} \mathbb N$, then $\mathbf{mtuple} A$ is the dependent function type, $$\prod_{i \colon \underline{n}} (\underline{m_i} \to A).$$

### Fork and Eval

Define $\mathrm{fork} : (A \to B)\to (A \to C) \to A \to (B \times C)$ as follows: if $f \colon A \to B$, $g \colon A \to C$, and $a \colon A$, then $\mathrm{fork} (f) (g) (a) = (f (a), g (a))$.

(A more standard definition of fork might take the domain to be $(A \to B)\times (A \to C)$, whereas we have described a "curried" version in order to support partial application.)

The fork function generalizes easily to dependent function types. Let $A$ be a type and for each $a \colon A$ let $B_a$ and $C_a$ be types. Define the dependent fork, denoted by $$\mathbf{fork} : \prod_{a : A} B_a\to \prod_{a : A} C_a \to \prod_{a : A}(B_a \times C_a),$$ as follows: if $f \colon \Pi_{a : A} B_a$, $g \colon \Pi_{a : A} C_a$, and $a \colon A$, then $\mathbf{fork} (f) (g) (a) = (f (a), g (a))\colon B_a \times C_a$. Since we use a curried definition, we can partially apply $\mathbf{fork}$ and obtain the expected typing relations, viz., $$\mathbf{fork} (f) \colon \prod_{a:A} C_a \to \prod_{a:A} (B_a \times C_a)\quad \text{ and } \quad \mathbf{fork} (f) (g) \colon \prod_{a:A} (B_a \times C_a).$$

Next, let $\mathbf{eval} \colon (A \to B) \times A$ denote function application; that is, $\mathbf{eval} (f, a) = f a$, if $f \colon A \to B$ and $a \colon A$. Thus, if $h \colon \prod_{a : A}(C_a \to D)$, $k \colon \prod_{a : A}C_a$, and $a\colon A$, then $$\mathbf{fork} (h)(k)(a) = (h(a), k(a)) \colon (C_a \to D) \times C_a, \text{ and }$$ $$\mathbf{eval} \circ \mathbf{fork} (h)(k)(a) = h(a)k(a) \colon D.$$

### General Composition of Operations on a Set

In universal algebra we deal mainly with finitary operations on sets. By an $n$-ary operation on the set $A$ we mean a function $f \colon A^n \to A$, that takes $n$ inhabitants of the type $A$ and returns an element of type $A$.

By the equivalence of the $\mathrm{ntuple}$ type and the function type $\underline{n} \to A$, we may represent the type of $n$-ary operations on $A$ by $(\underline{n} \to A) \to A$. Evaluating such an $f \colon (\underline{n} \to A) \to A$ at a tuple $a \colon \underline{n} \to A$ is simply function application, expressed by the usual rule (sometimes called "implication elimination" or "modus ponens").

If we let $a_i$ denote the value of $a$ at $i$, and if we identify $a$ with it's graph (the tuple $(a_0, \dots, a_{n-1})$), then $f a = f(a_0, \dots, a_{n-1})$.

Denote and define the collection of all finitary operations on $A$ by $$\operatorname{Op}A = \bigcup_{n<\omega} (A^n \to A)\cong \bigcup_{n<\omega} ((\underline{n} \to A) \to A).$$

We will now try to develop a formulation of general function composition that is more elegant and computationally practical than the standard formulation. Let us first briefly review the standard formulation of function composition. Let $f \colon (\underline{n} \to A) \to A$ be an $n$-ary operation on $A$, and suppose for each $0\leq i < n$ we have an operation $g_i \colon (\underline{k_i} \to A) \to A$. Then we define $f \circ (g_0, \dots, g_{n-1})$ in the following standard way: for each $$((a_{00}, \dots, a_{0(k_0-1)}), \dots, (a_{(n-1)0}, \dots, a_{(n-1)(k_{n-1}-1)}))\colon A^{k_0} \times \cdots \times A^{k_{n-1}},$$ \begin{align*}(f\circ &(g_0, \dots, g_{n-1}))((a_{00}, \dots, a_{0(k_0-1)}), \dots, (a_{(n-1)0}, \dots, a_{(n-1)(k_{n-1}-1)}))\ &= f(g_0(a_{00}, \dots, a_{0(k_0-1)}), \dots, g_{n-1}(a_{(n-1)0}, \dots, a_{(n-1)(k_{n-1}-1)})).\end{align*}

Not only is this notation tedious, but also it lends itself poorly to computation. To improve upon it, let us first consider the ntuple $(g_0, \dots, g_{n-1})$. This is an ntuple of operations from $\operatorname{Op}A$. If we denote by $g$ the function from $\underline{n}$ to $\operatorname{Op}A$ given by $g i = g_i$ for each $0\leq i < n$, then $g$ inhabits the following dependent function type: $$\prod_{i : \underline{n}} ((\underline{k_i} \to A) \to A).$$

Next, define the function $a$ as follows: $a i \colon \underline{k_i} \to A$ for each $0\leq i < n$ and for each $j\colon \underline{k_i}$, $a i j = a_{ij}$. Then the ntuple of arguments in the expression above can be identified with the tuple $a = (a 0, \dots, a (n-1))$ of functions. Thus $a$ has dependent function type $\prod_{i : \underline{n}} (\underline{k_i} \to A)$, and for each $i\colon \underline{n}$, we have $a i j = a_{ij}$.

Now, looking back at the section above, where we defined the fork and eval functions, we can see how to perform general composition using dependent types. If $g \colon \Pi_{i : \underline{n}} ((\underline{k_i} \to A) \to A)$, and $a \colon \Pi_{i : \underline{n}}(\underline{k_i} \to A)$, then $$\mathbf{fork} (g) (a) (i) = (g(i), a(i)) : ((\underline{k_i}\to A) \to A) \times (\underline{k_i}\to A)$$ and $\mathbf{eval} (\mathbf{fork} (g) (a) (i)) = g(i) a(i)$ has type $A$. Observe that the codomain $A$ does not depend on $i$, so the types $\Pi_{i:\underline{n}} A$ and $\underline{n} \to A$ are equivalent. Therefore, $\mathbf{eval} \circ \mathbf{fork} (g) (a)$ has type $\underline{n} \to A$. On the other hand, we have $$\mathbf{eval}\circ \mathbf{fork} (g) : \prod_{i : \underline{n}} (\underline{k_i} \to A) \to (\underline{n} \to A).$$ Thus, if we take an $n$-ary operation, $f\colon (\underline{n} \to A) \to A$, and an $n$-tuple of operations, $g\colon \Pi_{i : \underline{n}} ((\underline{k_i} \to A) \to A)$, then we can define the composition of $f$ with $g$ as follows: $$f [g] := f \circ (\mathbf{eval}\circ \mathbf{fork}(g)) : \prod_{i : \underline{n}}(\underline{k_i} \to A) \to A.$$ Indeed, if $a \colon \Pi_{i : \underline{n}}(\underline{k_i} \to A)$, then $\mathbf{eval}\circ \mathbf{fork}(g)(a)$ has type $\underline{n} \to A$, which is the domain type of $f$; therefore, $f (\mathbf{eval}\circ \mathbf{fork}(g) (a))$ has type $A$, as desired.